Tree Flora of Mudumalai Sanctuary, Tamil Nadu, Southern India - Suresh, H. S.; Dattaraja, H. S.; Sukumar, R. (Indian Forester, 1996)
A survey conducted on the tree flora of Madumalai Sanctuary, Tamil Nadu is given with brief notes.